A Mamoa da «Mama do Furo» (Figueira da Foz) - Vilaça, Raquel (Trabalhos de Antropologia e Etnologia, 2020)
The results obtained through the excavations carried out over the last two years in the barrow known as «Mama do Furo» (Figueira da Foz) are published in this article. This monument, as well as ali the others at the necropolis of «Serra da Boa Viagem», was already known last century. At that time, it was only partially excavated by the archaeologist Santos Rocha, of Figueira da Foz, who left some information registered. It consists of an impressive barrow (28 m diameter by 2,34 height), it is isolated; basically made out of a very hard and compact clay and has two «rings» of stone, one on the exterior bounding the barrow and the other in the interior around the chamber area, which was probably to give a greater equilibrium and stability to the supports. We must point out that the component blocks of the «ring» in the interior were rested on a layer of pure red clay, possibly with the intention of acquiring a better firmness, due to the high percentage of plasticity of the clay. From the megalithic structures of the Dolmen that once existed there, only two supports (both «in-situ» but broken) still remain; one of them is bent forward to the interior. It was a monument with a chamber and a passage grave, probably quite long, facing east/ southeast. The most important objects found were: 14 arrows heads made out of silex (mainly with triangular and biconcave bases); 23 blades (or fragments of blades also made ou of silex), some of which shining intensely on the retouched part due to a practical and effective use; two ceramic objects almost complete but without decorations and of primary shape.